A Biochemical Study on the Development of Actinidia deliciosa Callus by Combinations of Naphthalene Acetic Acid, 6-Benzylaminopurine and Indole-3-Butyric Acid - Topdemir, Aykut; Okutan, Tuba; Kirmizikaya, Gorkem; Yilmaz, Okkes (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2024)
In this study, different concentrations and combinations of auxin derivative naphthalene acetic acid (NAA), cytokinin derivative 6Benzylaminopurine (BAP) and indole-3-butyric acid (IBA) were applied to cotyledon explants of kiwifruit (Actinidia deliciosa). Phenolic compound, antioxidant activity, fatty acid composition and lipophilic molecule contents of callus cells were investigated. When the shoots of Actinidia deliciosa grown in a culture medium reached 5 cm, their cotyledons were used as explant source. Callus induction was achieved in culture media containing plant growth regulators (BBD) in different doses and combinations. According to the results of the analysis made with calli, the total phenolic content of the F group containing 0.5 mg L1 NAA + 1 mg L-1 BAP + 0.5 mg L-1 IBA combination was decreased compared to the control group (p<0.05), but it was significantly higher in the other groups. (p<0.001). Although DPPH and ABTS antioxidant capacity values were higher in the groups given NAA and BAP combination, it was determined that they were lower in the groups with NAA+BAP+IBA combination. The level of alpha-tocopherol, an antioxidant - effective lipophilic molecule, was higher in NAA and BAP groups applied at different concentrations (p<0.001), but decreased in NAA and BAP and NAA+BAP+IBA combination groups used in different concentrations (p<0.001). It was observed that phytosterol levels such as ergosterol, stigmasterol and betasitosterol decreased at different rates in the combination groups in which plant growth regulators (BBD) were applied. Although the palmitic acid ratio increased in most of the BBD groups compared to the control group in the fatty acid combination (p<0.01), no statistical difference was found in some BBD groups. While a decrease was observed in palmitoleic, stearic and linoleic acid ratios in the fatty acid composition of the groups in which different combinations of BBD were given, an increase was observed in linolenic acid ratios (p<0.05, p<0.01, p<0.001). As a result, it was determined that the auxin and cytokinin derivatives used at different rates on the callus formation of the kiwi plant had different effects on the biochemical metabolites of the callus tissue.
Keywords: Actinidia deliciosa; Micropropagation; Total phenolics; DPPH; Fatty acid composition